Islam dan Kapitalisme; Titik Temu dan Kritik Dalam Al-Qur’an - Habiburrahman Habiburrahman (Indonesian Journal of Religion and Society, 2019)
This paper discusses the point of view of Al-Quran on the spirit of capitalism because there is enormous imbalance between the reality of Muslims who are poor and spirit to rich. This study analyzed the interpretation of Indonesian scholars and how the spirit of capitalism relates to the Al-Quran. This research was a literature study that examined the interpretation of Indonesian scholars. It was descriptive-analytical. It explored in depth about these interpretations and related them to the spirit of capitalism in the Al-Quran. This study found the Al-Quran view of the spirit of capitalism. Humans are not only commanded pure worship to God but also pay attention to their daily life. Human do everything to obtain wealth due to their needs. This was the principle of capitalism by Ayn Rand through the theory of Max Weber. The spirit of capitalism is a human attitude in an effort to fulfill their needs. Thus, the author pointed the spirit of Al-Quran that teaches this is as the spirit of capitalism in the Al-Quran. However, Islam addresses capitalism by formulating an economic system based on Al-Quran.